2014
DOI: 10.1186/1742-4690-11-s1-o23
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to HTLV-1 basic leucine zipper factor (HBZ) in HTLV-1-infected individuals

Abstract: Enose-Akahata et al.: Humoral immune response to HTLV-1 basic leucine zipper factor (HBZ) in HTLV-1-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The frequency of the HBZ antibody was 0.88% (1/114) among the screeningpositive donors and 2.63% (1/38) among the confirmatory test-positive donors. Enose-Akahata and coworkers 11 reported that 10.34% (15 in 145) of asymptomatic HTLV-1 carriers exhibited antibody responses against the HBZ protein.…”
Section: Detection Of An Anti-hbz Responsementioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of the HBZ antibody was 0.88% (1/114) among the screeningpositive donors and 2.63% (1/38) among the confirmatory test-positive donors. Enose-Akahata and coworkers 11 reported that 10.34% (15 in 145) of asymptomatic HTLV-1 carriers exhibited antibody responses against the HBZ protein.…”
Section: Detection Of An Anti-hbz Responsementioning
confidence: 99%
“…Figure 1B shows the luciferase enzyme activities (indicated as RLUs) of the lysates of cells transfected with each of the vectors. We also constructed a plasmid that encoded the HBZ protein fused with Renilla luciferase at the N-terminus of HBZ (RLucHBZ), as reported previously, 11 to examine whether the antibody responses were affected by the order of the HBZ and Renilla luciferase proteins. The expression level of RLucHBZ was slightly less than that of HBZRLuc ( Fig.…”
Section: Expression Of Lips Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphoproliferation assay using carboxyfluorescein succinimidyl ester (CFSE) (CellTrace CFSE cell proliferation kit; Invitrogen) was performed as described previously. 18 PBMCs were labeled with CFSE, according to the manufacturer's instruction, and plated at 3 × 10 5 cells/well in 96-well round bottom microplates with defined concentrations of teriflunomide (0, 25, 50, and 100 μM). After culture for 4 and 5 days, the cells were stained with antibodies against CD3, CD4, CD8, and CD25 (all from BD Biosciences).…”
Section: Lymphoproliferation Assaymentioning
confidence: 99%
“…Enose-Akahata et al evaluated the immune response against HBZ in HTLV-I-infected individuals [ 122 ]. The immunoreactivity for HBZ was detected in subsets of all HTLV-I-infected individuals, but did not discriminate between asymptomatic carrier, ATLL and HAM/TSP.…”
Section: Introductionmentioning
confidence: 99%